2013
DOI: 10.1093/trstmh/trt044
|View full text |Cite
|
Sign up to set email alerts
|

T helper type 2 bias and type 17 suppression in primary dengue virus infection in infants and young children

Abstract: Age-related differences in the primary response to DENV, characterized by an immature Th2 polarization and Th17 suppression in infants, should be studied further in order to expand our understanding of the mechanism of dengue pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…The pattern of cytokine production follows a T helper type 1 (Th) or Th0 profile. These T cells may produce IFN‐γ, TNF‐α, IL‐2 and CC chemokine ligand 4 [CCL4; also known as macrophage inflammatory protein‐1β (MIP‐1β)], whereas the production of Th2 type cytokines, such as IL‐4 and IL‐13, is less common and less investigated . Studies have shown that CD8 + T cells specific to the DENV serotype of a previous infection appear to be preferentially expanded during a secondary infection .…”
Section: Immunological Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The pattern of cytokine production follows a T helper type 1 (Th) or Th0 profile. These T cells may produce IFN‐γ, TNF‐α, IL‐2 and CC chemokine ligand 4 [CCL4; also known as macrophage inflammatory protein‐1β (MIP‐1β)], whereas the production of Th2 type cytokines, such as IL‐4 and IL‐13, is less common and less investigated . Studies have shown that CD8 + T cells specific to the DENV serotype of a previous infection appear to be preferentially expanded during a secondary infection .…”
Section: Immunological Featuresmentioning
confidence: 99%
“…These T cells may produce IFN-c, TNF-a, IL-2 and CC chemokine ligand 4 [CCL4; also known as macrophage inflammatory protein-1b (MIP-1b)], whereas the production of Th2 type cytokines, such as IL-4 and IL-13, is less common and less investigated. [31][32][33] Studies have shown that CD8 + T cells specific to the DENV serotype of a previous infection appear to be preferentially expanded during a secondary infection. 34,35 Analysis of the functional phenotypes of CD8 + T cells in DHF cases have revealed that cross-recognition is associated with reduced cytolytic/cytotoxic activity without a significant effect on cytokine production.…”
Section: Immunological Featuresmentioning
confidence: 99%
“…The latter are grouped by the World Health Organization (WHO) into three levels of disease severity: dengue without warning signs (DWoWS), a febrile illness frequently associated with rash and joint pain; dengue with warning signs (DWWS), in which the patient may also experience hemorrhage, swelling, hepatomegaly, and/or an increase in hematocrit and thrombocytopenia; and the potentially fatal severe dengue (SD), which may include severe bleeding, shock, organ failure, and respiratory distress . Differences in clinical manifestations and severity have been associated with secondary heterologous DENV infection, patient age, and virus serotype, though the underlying mechanisms of disease enhancement are still not fully characterized.…”
Section: Introductionmentioning
confidence: 99%
“…The purification of DENV envelope (E) protein ectodomains was performed as previously described (Talarico et al, 2013). Protein-specific immunoassays were conducted similarly to those described in previous publications (Delgado et al, 2009, Polack et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…To determine anti-DENV neutralizing antibodies in sera from DENV-1 and DENV-2 immunized mice, a plaque reduction neutralization assay against DENV serotypes was performed as previously described, with some modifications (Talarico et al, 2013). Briefly, mice sera were heat-inactivated at 56 °C for 30 min and four-fold serial dilutions of the serum samples (1/20 to 1/5120 in MEM) were mixed with an equal volume containing 100 PFU of DENV-2 in MEM containing 2% FBS.…”
Section: Methodsmentioning
confidence: 99%